Asenapine in bipolar I disorder: evidence and place in patient management. (January 2013) - Samalin, Ludovic; Charpeaud, Thomas; Llorca, Pierre-Michel
Asenapine is a new second-generation antipsychotic approved in September 2010 by the European Medicines Agency for the treatment of bipolar disorder. It demonstrated significant efficacy compared with placebo in acute mania or mixed episodes as monotherapy or adjunctive therapy to mood stabilizers (lithium or valproate). Early improvement was noted at day 2 and was strongly associated with response and remission at week 3. Asenapine also appeared effective in treating acute mania in older patients with bipolar disorder. Post hoc analyses of asenapine showed efficacy in treating depressive symptoms during manic or mixed episodes compared with placebo. The efficacy of asenapine in patients with acute mania appeared to remain constant during maintenance treatment. Asenapine was reasonably well tolerated, especially with regard to metabolic effects. There were minimal signs of glucose elevation or lipid changes and the risk of weight gain appeared limited. The prolactin elevation was smaller than other antipsychotic comparators. Only oral hypoesthesia occurred as a new adverse event compared with other second-generation antipsychotics. Asenapine presents several advantages over other second-generation antipsychotics, such as sublingual formulation, early efficacy and good metabolic tolerability. This tolerability profile confirms the heterogeneity of the second-generation antipsychotic class and supports the view of some authors for the need to re-evaluate the boundaries of this group.